Uncovering Polygamy: A New Perspective from Al-Majmuʼ Syarh al-Muhadzdzab an-Nawawi through the Lens of Maqāṣid al-Sharīʿah by Jasser Auda - Muhammad Danil; Al Ikhlas Al Ikhlas; Desi Yusdian; Fathur Rahmi (Universitas Negeri Padang, 2026)
Polygamy remains a persistently contested issue within Islamic jurisprudence, intersecting legal, ethical, and social dimensions. This study examines the concept of polygamy as articulated by Imām al-Nawawī in Al-Majmuʼ Syarh al-Muhadzdzab a seminal encyclopedic work of Shāfiʼī fiqh and evaluates it through the systemic Maqāṣid al-Sharīʿah framework of Jasser Auda. Employing a descriptive-analytical library research method followed by a comparative-analytical approach (muwāzanah), this study systematically analyses primary and secondary sources to identify convergences and divergences between classical jurisprudential reasoning and contemporary maqāṣid thought. The findings reveal that al-Nawawī permits polygamy for up to four wives, conditioning it strictly upon material justice (qism and nafaqah) while explicitly recommending monogamy as a prudential preference to avert injustice. Jasser Auda's systemic approach, which prioritises human flourishing, harm reduction (dafʼ al-mafāsid), and contextual holistic justice encompassing emotional, psychological, and social well-being provides a substantially expanded evaluative lens. The comparative analysis demonstrates that, while both perspectives share the foundational telos of justice and welfare, Auda's framework demands an empirical assessment of real-world outcomes, rendering polygamy a highly constrained exception rather than a general permission in contemporary contexts. This study contributes to ongoing scholarly dialogue on the reform of Islamic family law by bridging classical and contemporary maqāṣid methodologies.